PENGEMBANGAN MODEL PENDIDIKAN AGAMA HINDU BERBASIS MULTIKULTUR PADA SEKOLAH MENENGAH ATAS DI PROVINSI BALI - I Wayan Mudana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
A religious discordance case which is very thick with the scent of a deterministic stateintervention accompanied by inter-religious conflict in the social and cultural lifemarks theweakness of multicultural mindset of a nation. The aim of this research is to develop amulticultural-based educational model of Hinduism subject by using interactive model. OnewayAnavaanalysiswasconductedanditwasfoundthatmulticultural-basededucationalmodelofHinduismsubjectbyusinginteractivemodelhadgivensignificantlymoreeffectiveresult(=74,76) than the conventional model( =69,16). The factors that can support and inhibitmulticultural-based educational model of Hinduism subject by using interactive model can befrom teachers, students and educational facilities and infrastructures. Through this research, itis hoped that teacher will insert multicultural education especially in Hinduism subject giventhe frequent occurrence of ethnicity, religion, race, and inter-group relations conflicts in Indonesia,because multicultural education prepares students to face problems regardless of religiousbackground, ethnicity, and culture.